C-peptide and epicardial adipose tissue in dialysis-dependent chronic kidney disease patients - D’Marco, Luis; Checa-Ros, Ana; Locascio, Antonella; Joshua Okojie, Owahabanun; Viejo, Iris; Bermúdez, Valmore; Karohl, Cristina; Raggi, Paolo (Frontiers in Medicine, 2025)
BackgroundSeveral studies suggest that C-peptide (CP) is involved in regulating lipolysis, adipokine release, and other functions in the adipose tissue. On the other hand, organ-specific adipose tissues, such as the epicardial adipose tissue (EAT), have been reported as an independent cardiovascular risk factor in patients on dialysis. This study aimed to evaluate the association between CP, EAT volume, and coronary artery calcification (CAC) as markers of cardiovascular risk, on subjects with type 2 diabetes receiving insulin and dialysis.MethodsThis is a retrospective study on 62 patients with chronic kidney disease (CKD) stage 5 on dialysis awaiting kidney transplantation and referred for cardiovascular risk stratification at the Emory University Hospital. Computed tomography (CT) was used to assess CAC and to measure EAT volume. Demographic and anthropometric data were collected from all patients through record review.ResultsThe mean patient age was 43 ± 11 and 55% were women. None of the serum analytical parameters correlated with CP. Subjects with higher BMI exhibited higher levels of CP. EAT volume strongly correlated with CP levels, and it was significantly correlated with CAC. On the contrary, no correlation was found between CP and CAC.ConclusionThe significant association between EAT volume and CP suggests a potential role of CP in the cardiovascular physiopathology of patients with ESKD on dialysis. Insufficient statistical power was probably the cause of the lack of association of CP with CAC. Observational prospective studies are required to characterize CP as a cardiovascular risk marker in patients with ESKD.